Pomoc społeczna i jej biblijne prawzory. - Nitecki, Stanisław (PRAWO i WIĘŹ, 2025)
Social assistance is an instrument that is available to a specific community that creates a society, with the use of which the community provides forms of support for members of this community who require it. The formalized expression of the community is the state, its bodies and the institutions created by them. Social assistance is the institution with the use of which the state takes action to support people in a difficult situation. The necessity of taking such actions is also foreseen in the Bible. It is the document that refers to God and to what His vision of man is and how man should live. Within this vision, one can see the existence of an institution created by the community, and aimed at supporting those who are unable to meet their needs on their own. The occurrence of the key principle of social assistance, namely the principle of subsidiarity, is noticed, and in a very radical form. An important element is to draw attention to the necessity of building a social infrastructure, with the use of which the most essential needs of members of a given community will be met.